Fully Flexible, Low-Cost, Environmentally Friendly Yarn-Based Inp/Ag Nw Photodetectors for UV-Visible Light Detection - Savaş, M.; Akrema, A.; Ocal, S.K.; Erdem, T. (SPIE, 2025)
We report the fabrication and investigate of a novel photodetector using a heterostructure of InP quantum dots (QDs) and silver nanowires (Ag NWs) incorporated into yarn. This device is simple, scalable, low-cost, flexible, and functions under ambient conditions. Ag NWs and red-emitting InP QDs were separately synthesized via chemical methods and mixed in a specific ratio to coat functional yarns, which were then knitted into fabrics. The photodetector benefits from the excellent electrical conductivity of Ag NWs and the strong optical absorption of InP QDs. It shows enhanced photoelectric response in both UV and visible regions. At 405 nm illumination, the device achieves a photoresponsivity of 5.8 mA W-1 and a detectivity of 2 × 1010 Jones-values comparable to or exceeding those of similar devices. The enhanced performance is attributed to efficient charge transfer enabled by favorable band alignment between Ag NWs and InP QDs, along with synergistic effects from nanostructure dimensionality and quantum confinement. The device's combination of flexibility, sensitivity, and cost-efficiency makes it a strong candidate for wearable UV-visible photodetectors. © 2025 SPIE. All rights reserved.
SPIE
Keywords: Photodetectors; Quantum Dots; Silver Nanowires; Sustainable Optoelectronics; Wearable Optoelectronics; Yarn